Performance of a Hybrid Ichthyoid-Waterjet Articulated Propulsor - SZMIDT, Tomasz (Engineering Transactions, 2025)
The concept of a bioinspired ichthyoid-waterjet propulsor for autonomous underwater vehicles (AUVs) is investigated. The propulsor consists of an articulated fluid-conveying pipe with a propulsive fin at the end. Water drawn into the hull is accelerated to a supercritical velocity, which yields flutter vibrations of the propulsor resembling the motion of a swimming fish. The fin acts on the surrounding water and generates thrust. At the same time, the ejected water produces recoil. Using the proposed dynamical model, three types of propulsors for different swimming speeds are investigated. At low swimming speeds, the propulsive force generated by the propulsors can be up to 30% higher than the thrust of a conventional waterjet propulsor with the same physical parameters. However, this advantage in the generated thrust decreases with the swimming speed increase. The results are obtained by analyzing the approximation of the bifurcating solution and numerical simulations of the differential equation governing the dynamics.